Metonymy in scientific linguistic discourse - Gabidullina, Alla; Sokolova, Anastasiia; Kolesnichenko, Elena; Zharikova, Marina; Shlapakov, Oleh (Linguistics and Culture Review, 2021)
The purpose of the article was to show the features of the functioning of different types of metonymy in scientific linguistic discourse, which is understood as a verbalized epistemic situation common to the scientific sphere of communication, taken in the entire totality of linguistic and extralinguistic factors and enshrined in the form of texts (oral and written ones). The article deals with metonymy from the point of view of langue / parole: lexicalized metonymy in langue is a semantic transposition mechanism on contiguity and carries out a terminological nomination; discursive metonymy in parole becomes the result of syntagmatic contiguity of syntactic constructions. Linguistic metonymic terms are grouped by types of knowledge: declarative and procedural ones. The shifts of meaning between the logical terms “object”, “subject”, “general” and “specific”, “abstract” and “concrete”, “form”, “content”, etc., directed towards each other, are observed in metonymic terms of declarative type. Metonymy can reflect the processes due to the causality between adjacent objects. Transitional phenomena between lexicalized (linguistic) and discursive (speech) metonymy reflect those models that contain onyms; they are related to the designation of the subject of knowledge (linguist) and his scientific discovery.